Exploring pre-service teachers’ beliefs about EAP instruction in China – A case study - Lucas Kohnke; Di Zou; Ruofei Zhang (International Journal of Educational Research Open, 2022)
Despite English being a priority in China and extensive policy changes over the past decades, English language teaching and learning at Chinese tertiary institutions remains insufficient. College English (CE) courses focus on holistic and humanistic education by teaching English for general purposes. However, they are often inefficient and unable to serve university students’ needs. Researchers and practitioners alike call for a transition from CE to English for Academic Purposes (EAP). This study explored pre-service teachers’ perceptions of EAP provision in mainland China through a qualitative, interpretive approach. Sixteen pre-service teachers, who completed their bachelor's education in China and master's education in Hong Kong, participated in semi-structured interviews, sharing their experiences and discussing the challenges and opportunities for EAP to serve as a replacement for or supplement to CE. Thematic analysis revealed complexities comprising current education, the traditional, top-down system, learning styles, status, and lack of professional development opportunities. This paper discusses the challenges of implementing EAP in mainland China in an effort to help policymakers, researchers, and practitioners identify the way out.